High-Performance Optical NOR Gate with SOA-MZI - Amer Kotb; Kyriakos E. Zoiros; Wei Chen (Photonics)
In this paper, we propose a novel design for a NOR gate using a semiconductor optical amplifier combined with a Mach–Zehnder interferometer. By utilizing two inverting input signals, the system achieves the NOR logic function, simplifying the overall architecture and reducing component complexity. The gate’s performance is evaluated at 80 Gb/s, achieving a high-quality factor of 23.47, demonstrating superior signal integrity and reliability. We analyze the influence of key parameters on the gate’s functionality and assess the impact of amplified spontaneous emission on system performance. This study provides a comprehensive evaluation of the NOR gate and contributes to developing efficient, cost-effective solutions for complex optical logic circuits.